Pendidikan Islam dalam Persepektif KH. Abdul Fattah Hasyim; Refleksi Historis Perkembangan Pendidikan di PP. Bahrul 'Ulum - Muhammad Asrori Ma'sum (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2013)
Boarding school Bahrul Ulum Tambakberas Jombang standing around in 1825 by Kyai Abdussalam or known as the leader in the hamlet Gedang Shoehah Tambakberas village is one of the schools that proliferated tradisioanal the colonial period before Indonesia's independence. This study uses sociological approach, philosophical, and theological. thoughts or views of Kyai Abdul Fattah education looks heavily influenced by the Islamic intellectual tradition of the late 19th century and the Islamic intellectual tradition of the pre- modern period especially KH.Hasyim Asy'ari as core teachers. Education is not only based on the knowledge transfer between clerics and students alone, but there needs to be 'uswah' from yourself. The fact is what makes the Kyai Abdul Fatah crowned as the Father of Education Bahrul Ulum because he was able to lay the foundations of education to all the people around him (family, students and the community).